2005
DOI: 10.1038/sj.hdy.6800763
|View full text |Cite
|
Sign up to set email alerts
|

Using mating designs to uncover QTL and the genetic architecture of complex traits

Abstract: Analysis of quantitative trait loci (QTL) affecting complex traits is often pursued in single-cross experiments. For most purposes, including breeding, some assessment is desired of the generalizability of the QTL findings and of the overall genetic architecture of the trait. Single-cross experiments provide a poor basis for these purposes, as comparison across experiments is hampered by segregation of different allelic combinations among different parents and by contextdependent effects of QTL. To overcome th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 61 publications
5
76
2
Order By: Relevance
“…Sampling strategies should reflect the goal of the research. Sampling fewer families with more progeny per family seems to provide higher power for QTL detection, but sampling more families with fewer progeny seems to provide more reliable estimates of the overall genetic architecture (for example, general and specific combining ability variances), allele number and QTL variance (Wu and Jannink, 2004;Verhoeven et al, 2006). Different analysis approaches have different optimal sampling strategies as well.…”
Section: Heritability Estimatesĥmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling strategies should reflect the goal of the research. Sampling fewer families with more progeny per family seems to provide higher power for QTL detection, but sampling more families with fewer progeny seems to provide more reliable estimates of the overall genetic architecture (for example, general and specific combining ability variances), allele number and QTL variance (Wu and Jannink, 2004;Verhoeven et al, 2006). Different analysis approaches have different optimal sampling strategies as well.…”
Section: Heritability Estimatesĥmentioning
confidence: 99%
“…component of genetic variation for all traits. However, if marker effects are to be tested as nested within families, a minimum sample of at least 40 progeny per family seems necessary to maintain good power of QTL detection (Wu and Jannink, 2004;Verhoeven et al, 2006;Yu et al, 2008). Larger sample sizes could be drawn from mapping families with greater parental PD, as some traits do exhibit a moderate relationship between PD and GVC.…”
Section: Heritability Estimatesĥmentioning
confidence: 99%
“…Apart from the LD generated by the sampling of the parents, LD will also inevitably arise in designs with multiple segregating populations owing to the mating design (Verhoeven et al, 2006). Within segregating populations alleles at unlinked loci will be in linkage equilibrium, but they will be in LD across populations.…”
Section: Properties Of the Jlam Populationmentioning
confidence: 99%
“…This can create a population structure and thus an inter-chromosomal LD that was lower in the balanced DIA design than in the SRR design (Supplementary Figure 7). Verhoeven et al (2006), therefore, concluded that it is essential to account for population structure in the biometrical model.…”
Section: Properties Of the Jlam Populationmentioning
confidence: 99%
See 1 more Smart Citation